Multi-annual prediction of drought and heat stress to support decision making in the wheat sector - Balakrishnan Solaraju-Murali (Nature Portfolio, 2021)
Abstract Drought and heat stress affect global wheat production and food security. Since these climate hazards are expected to increase in frequency and intensity due to anthropogenic climate change, there is a growing need for effective planning and adaptive actions at all timescales relevant to the stakeholders and users in this sector. This work aims at assessing the forecast quality in predicting the evolution of drought and heat stress by using user-relevant agro-climatic indices such as Standardized Precipitation Evapotranspiration Index (SPEI) and Heat Magnitude Day Index (HMDI) on a multi-annual timescale, as this time horizon coincides with the long-term strategic planning of stakeholders in the wheat sector. We present the probabilistic skill and reliability of initialized decadal forecast to predict these indices for the months preceding the wheat harvest on a global spatial scale. The results reveal the usefulness of the study in a climate services context while showing that decadal climate forecasts are skillful and reliable over several wheat harvesting regions.